2021
DOI: 10.18502/acta.v59i11.7780
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pulmonary Function Test (PFT) in Patients Affected by Severe COVID-19 Pneumonia: 6 to 12 Weeks After Discharge

Abstract: The most lethal adverse effect of COVID-19 is acute respiratory distress syndrome, which can lead to rapid death. This symptom even causes concern for patients who have recovered and have been discharged. Therefore, it is obligatory to test and monitor variations in their lungs’ function after recovery. In this study, we evaluated the pulmonary function of 64 patients with severe COVID-19, six weeks to 3 months after discharge. Pulmonary function parameters were measured by spirometry and body box according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Babadi et al's study on severe COVID-19 pneumonia patients found 3.1% with an obstructive pattern, 40.63% with a restrictive pattern, and 6.25% with a mixed pattern. These findings underscore the diverse pulmonary function outcomes in individuals recovering from severe COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Babadi et al's study on severe COVID-19 pneumonia patients found 3.1% with an obstructive pattern, 40.63% with a restrictive pattern, and 6.25% with a mixed pattern. These findings underscore the diverse pulmonary function outcomes in individuals recovering from severe COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 88%
“…The use of non-invasive and inexpensive procedures such as PFT, which includes FEV1, FVC, FEV1/FVC ratio, and the six-minute walk test, has proven valuable in identifying residual lung disease in individuals post lung infections, including COVID-19. Several studies, including those by Truffaut et al [ 14 ], Zhao et al [ 15 ], and Babadi et al [ 16 ], have demonstrated the persistent impact on lung function and other parameters in post-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%